A victory in theory, loss in practice: struggles for political representation in the Lake Baringo-Bogoria Basin, Kenya. Issue 1 (2nd January 2016) - Little, Peter D.
ABSTRACT: This article addresses political rights and identity among Il Chamus of Baringo District, Kenya, a small group of agro-pastoralists related to the Maasai. It discusses an important 2006 judicial ruling from the High Court of Kenya that specified a political constituency and national representation for the community, and shows how the state and its actions undermined its implementation. By examining the historical events and struggles leading up to the court ruling and the local violence associated with it, the article describes how Il Chamus have been forced to negotiate – even publically legislate – their histories and identities (indigeneity) to make claims to citizenship and territory. It concludes with a discussion of the impacts of the new 2010 constitution on the Il Chamus political movement and those of other minority and indigenous groups who have petitioned for increased political representation during the last two decades.